Survival of hepatitis A virus on human hands and its transfer on contact with animate and inanimate surfaces. - Mbithi, J N (1992)
The survival of hepatitis A virus (HAV; strain HM175) on the hands of five volunteers was determined by depositing 10 microliters of fecally suspended virus on each fingerpad and eluting the inoculum after 0, 20, 60, 120, 180, and 240 min. The amount of virus recovered from each fingerpad at 0 min was approximately 6.0 x 10(4) PFU. At the end of 4 h, 16 to 30% of the initially recoverable virus remained detectable on the fingerpads. HAV inocula (10 microliters; approximately 1.0 x 10(4) PFU) placed on fingerpads or 1-cm-diameter metal disks were used to determine virus transfer to clean surfaces upon a 10-s contact at a pressure of nearly 0.2 kg/cm2. When the inoculum was dried for 20 min, virus transfer from fingerpad to fingerpad, fingerpad to disk, and disk to fingerpad ranged from 2,667 to 3,484 PFU, while 0 to 50 PFU could be transferred after 4 h of drying. Elevation of the contact pressure alone from 0.2 to 1.0 kg/cm2 resulted in an approximately threefold increase in the amount of virus transferred. Incorporation of friction (10 half turns of the finger during 10 s of contact) with the low and high levels of pressure gave two- and threefold increases in the PFU of virus transferred, respectively. Pressure and friction were found to significantly affect HAV transfer (F = 33.98; P less than 0.05), irrespective of the mode of transfer used. No statistically significant interaction was observed between mode of transfer and pressure or friction. The findings of this quantitative study suggest that human hands may play an important role in the direct as well as the indirect spread of HAV.